Identifikasi Jamur Patogen Penyebab Penyakit Layu Pucuk pada Tanaman Adenium spp. di Kota Denpasar dan Potensi Pengendaliannya dengan Jamur Antagonis - SUGIARTA, DWI; SUDIARTA, I PUTU; SUNITI, NI WAYAN; SUPUTRA, I PUTU WIRYA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2021)
Identification of Pathogenic Fungi  that cause  Wilt ing  Diseases on  Adenium  spp.   Shoot in Denpasar City and  the  Potential Control with  A ntagonist ic  Fungi Ornamental plants of Adenium, known as  kamboja Jepang  have various types of flowers and stem shapes and have become unique ornamental plants in Indonesia. Adenium plants that grow in Denpasar City showed the symptoms of pathogenic fungi like wilting on the shoots. This study aims to identify the pathogenic fungi that cause major diseases in  Adenium  spp. in the area of ??Denpasar City. The activities carried out in this study were (1) sampling, (2) isolation of the pathogenic fungi from symptomatic Adenium plant, (3) pathogenicity test, (4) morphological identification of pathogenic fungi, and (5) inhibition test of the antagonistic fungi against the pathogenic fungi. This research was conducted in Denpasar City and the Plant Disease Laboratory, Faculty of Agriculture, Udayana University. The results of this study were successful in identifying  Fusarium  sp. as a pathogen that causes wilting of the shoots or dieback. The potential for biological control by utilizing antagonistic fungi showed that  Gliocladium  sp. can suppress the growth of pathogenic fungi  Fusarium  sp. up to > 87% and  Trichoderma  sp. up to > 88 %.